A design methodology for side wall failure of RHS truss X-joints accounting for compressive chord pre-load. (1st November 2016) - Cheng, Shanshan; Becque, Jurgen
Highlights: A design methodology for equal-width RHS X-joints is presented. Effect of compressive chord pre-load is investigated. Elastic local buckling stress of the side wall is used to define slenderness. FE modelling is applied to conduct parametric studies. Reliability analysis is carried out to ensure a target reliability level according to Eurocode and AISI. Abstract: This paper presents a design methodology for equal-width RHS X-joints failing by side wall buckling, with a particular focus on the effect of a compressive chord pre-load. A slenderness parameter is thereby defined based on the elastic local buckling stress of the side wall, idealized as an infinitely long plate under a patch loading transferred from the brace member in combination with a uniform chord pre-load. A Rayleigh-Ritz approximation is used to obtain a closed form solution. The proposed design equation is verified against finite element results over a wide range of wall slenderness values and is demonstrated to yield excellent predictions. Finally, a reliability analysis is performed using the first order reliability method (FORM) within the framework of both the Eurocode and the AISC Specification to ensure the proposed equation possesses the required level of safety. The proposed equation strongly outperforms the current CIDECT design rule for side wall buckling and also further extends the range of applicability to a wall slenderness ratio of up to 50.